Integration of Fintech and Sharia Factoring Based on Maqaṣid al-Shari‘ah for MSME Financing - Adriani, Siti Kamiliyah; Mugiyati, Mugiyati (Universitas Trunojoyo Madura, 2025)
The limited integration between fintech innovation and Sharia factoring within a comprehensive maqāṣid al-sharī‘ah framework constitutes a significant gap in Islamic finance research. This study aims to develop an integrative normative-conceptual framework that explains how fintech-based invoice financing can strengthen efficiency, transparency, financial inclusion, and Sharia compliance in MSME financing. The research employs a qualitative method using a normative-conceptual approach through library research. The data consist of secondary academic sources, including 35 peer-reviewed journal articles, books, and research reports, as well as 7 institutional documents from OJK, KemenkopUKM, AFPI, and Islamic fintech platforms published between 2018–2025. Data were analyzed using content analysis through reduction, categorization, and critical interpretation based on maqāṣid al-sharī‘ah. The findings indicate that the integration of blockchain, smart contracts, digital escrow systems, and Sharia contractual structures such as wakālah bil ujrah, murābaḥah, and qard ḥasan enhances transparency, risk mitigation, and access to MSME financing. However, regulatory standardization and digital Sharia governance remain limited. The study implies the need for harmonized regulatory frameworks and strengthened digital Sharia supervision to ensure that fintech innovation substantively achieves taḥqīq al-maṣlaḥah within the Islamic financial ecosystem.